The Experiment of Jepara Troso Woven in Local Wisdom - Sarwono, Sarwono; Prameswari, Nadia Sigi; Darwoto, Darwoto; Akhmad, Zunaila; Hassan, Hanisa (Harmonia: Journal of Arts Research and Education, 2023)
Troso woven cloth, located in Troso village, Jepara city, is one of the various Indonesian cultural heritages first discovered in AD. The purposes of this study are: 1) to investigate the woven cloth and its uses, the relationship between woven cloth with cultural and religious traditions, and the relationship between the woven cloth and local identity; 2) to design a new motif of Troso woven cloth that incorporates the elements of Jepara culture. The study used a practice-based research approach. The data were collected by purposive sampling technique. The results showed that the local community commonly uses woven fabric products as decorative. Troso cloth is also used to design attires, gamis dresses, or koko shirts for the feast day or formal events. The craftsmen of Troso woven fabrics made in Jepara primarily receive orders with motifs from other regions, including Bali, Sumatra, and Kalimantan. In contrast, the original woven fabric motifs distinctive from Troso are rarely known to the general public. The study formulates a new digital-based motif of the Troso fabric pattern that displays the iconic elements of Jepara city. The iconic depictions of Jepara are in the form of turtles, Jepara wooden carvings, and wave patterns. This research is expected to elevate the Troso fabric’s identity as a local identity of Jepara city and contribute to the Troso village community to develop the Troso fabric unique to the region.